1998
DOI: 10.1209/epl/i1998-00429-5
|View full text |Cite
|
Sign up to set email alerts
|

Steady state of atoms in a monochromatic elliptically polarized light field

Abstract: An analytical and invariant expression is given for the steady-state density matrix of free atoms in a monochromatic radiation field with arbitrary intensity and arbitrary elliptical polarization. The field drives the closed transition F → F + 1, with arbitrary values of F . This is the only class of transitions where a closed analytical expression for the steady state was lacking. Some applications of this result are indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The problem of steady state population redistribution among magnetic sublevels of fine or hyperfine V-type systems induced by intense linearly, circularly, or elliptically polarized excitation has been addressed starting from the 80-s in several theoretical papers [2][3][4][5]. These calculations show that the redistribution of populations of magnetic sublevels caused by sufficiently long action of an intense linearly-polarized laser radiation on atomic medium with V-type system of magnetic sublevels (transition from ground the state F = F to the excited state F = F + 1), after multiple cycles of absorption and spontaneous emission among different magnetic sublevels ("Zeeman pumping") leads to redistribution of population towards magnetic sublevels with small | F | values and tends to equalize the populations of particular ground and excited-state sublevels linked by linearly-polarized radiation.…”
Section: Redistribution Of Population Of Magnetic Sublevels and Partimentioning
confidence: 99%
“…The problem of steady state population redistribution among magnetic sublevels of fine or hyperfine V-type systems induced by intense linearly, circularly, or elliptically polarized excitation has been addressed starting from the 80-s in several theoretical papers [2][3][4][5]. These calculations show that the redistribution of populations of magnetic sublevels caused by sufficiently long action of an intense linearly-polarized laser radiation on atomic medium with V-type system of magnetic sublevels (transition from ground the state F = F to the excited state F = F + 1), after multiple cycles of absorption and spontaneous emission among different magnetic sublevels ("Zeeman pumping") leads to redistribution of population towards magnetic sublevels with small | F | values and tends to equalize the populations of particular ground and excited-state sublevels linked by linearly-polarized radiation.…”
Section: Redistribution Of Population Of Magnetic Sublevels and Partimentioning
confidence: 99%
“…It has been shown that the dark state exists even for atoms with complicated Zeeman substructure interacting with elliptically polarized light [51,52,53,54,55,56]. Here we recall the analytical expressions for this dark state and the corresponding eigenvalues.…”
Section: Analysis Of Nmor For the Casementioning
confidence: 99%
“…It should be noted that in principle, the stationary distribution of ′ µµ ρ (and hence ˆκ ρ ) for arbitrary S and g j , found in [1, [6][7][8][9], allows the light-induced forces acting on the atom and the susceptibility tensor of the medium to be determined. In this regard, we emphasize that investigations into the characteristic times entering into Eq.…”
Section: Problem Formulationmentioning
confidence: 99%